The evaluation of the earthquake awareness of the secondary school students in Istanbul [Istanbul'da ortaögretim ögrencilerinin deprem bilincinin degerlendirilmesi] - (:unkn) unknown (T.C. Milli Egitim Bakanligi, 2015)
This study aims to evaluate the earthquake awareness of students at the end of secondary education in Istanbul. In the study first a survey was prepared to measure the earthquake related knowledge, attitudes, and behaviors of the students and then it was conducted on 836 11th and 12th grade students in 11 high schools in four different districts of Istanbul. The study concluded that the knowledge, attitude, and behaviors of the students are not sufficient to create an awareness of earthquake to an extent that it will be useful to save their lives from a possible earthquake. Providing students with a lifelong awareness of earthquake will only be possible if teaching and learning activities are planned and sustained with this awareness targeted. Therefore, the primary and secondary education of Turkey should be evaluated and empowered again with its curriculums, materials, methods, and textbooks in order to provide students with a more efficient awareness of earthquake.
Keywords: Earthquake awareness; Geography education; Istanbul; Secondary education